Ho Chi Minh’s philosophical thought on self-criticism, criticism and its implications for contemporary Vietnam - Linh, Huynh Tuan (Kalágatos, 2026)
Ho Chi Minh, the revered hero of Vietnam, a global cultural icon, and founder of the Democratic Republic of Vietnam, devoted his life to national liberation and the fight for oppressed peoples worldwide. He emphasized training cadres and Party members to stay loyal to the nation, uphold revolutionary morality, and maintain the Party’s purity. He advocated regular self-criticism and criticism to promote personal and organizational growth. Today, as Vietnam deeply integrates globally and faces the market economy’s influence, some cadres and Party members show signs of moral and lifestyle degradation. Studying Ho Chi Minh’s philosophy on self-criticism and criticism is thus urgently needed. It provides a theoretical and practical framework to educate and refine cadres and Party members, enhancing political integrity, organizational discipline, and public trust in the Party’s leadership. This approach ensures the Party remains a steadfast force in guiding Vietnam forward.